1833. Impact of Antibiotic Stewardship on Antimicrobial Use for Urinary Tract Infection at a Veteran's Affairs Long-Term Care Facility. (26th November 2018) - Sandhu, Avnish; Kuhn, Ryan; Aranha, Anil; Cooper, Christopher; Dhar, Sorabh
Abstract: Background: Urinary tract infections (UTI) are common infections in long-term care facilities (LTCF) and can lead to increased antibiotic use and resistance. The impact of antimicrobial stewardship programs (ASP) interventions in the appropriate selection of antimicrobials for the treatment of UTIs is unclear. Methods: A prospective review was conducted at a 60-bed LTCF from an urban Veteran's Affairs Medical Center. The review followed analysis of antimicrobial selection and resistance patterns from this ward with implementation of an electronic medical record-based clinical decision support tool (EMR-CDS) for the treatment of UTI. Antibiotics were divided into two groups: guideline recommended and discouraged. Antibiotic use data (days of therapy (DOT)/1, 000 patient-days (PD)) was compared between the two groups in the pre-intervention and the post-intervention periods (January 2014 to December 2015 and August 2016 to March 2018, respectively) to determine the impact of the ASP intervention. Antimicrobial susceptibilities were also compared. Results: A reduction in total antimicrobial use from 48.61 to 25.62 DOT/1, 000 PD ( P < 0.001) was seen. Overall, guideline discouraged antibiotic use decreased 59% from 30 to 12.3 DOT/1, 000 PD ( P < 0.001) compared with guideline recommended antibiotic, which decreased by 29% from 18.65 to 13.3 DOT/PD ( P < 0.001). Guideline recommended antibiotics with increased usage during the study period included cephalexin (2.34 to 6.35 DOT/1, 000 PD; P < 0.001) (Figure 1). The percentage of appropriately prescribed antibiotics increased from 38.4% to 51.9% ( P < 0.001) between the pre- and postintervention periods. The greatest reduction in guideline-discouraged antibiotics use was cefuroxime from 17 to 1.58 DOT/1, 000 PD ( P < 0.001). Antimicrobial susceptibility increased in both antibiotic recommended and discouraged groups (25.8% and 26.8%) (Figure 2). Conclusion: Targeted ASP interventions in LTCFs leveraging antimicrobial resistance patterns, high-risk antimicrobials, and EMR-CDS support systems are successful methods for reducing total antimicrobial use, increasing appropriate antimicrobial prescribing, and decrease resistance. Disclosures: All authors: No reported disclosures.